THE DEVELOPMENT OF HADITH SCHOLARSHIP IN MAWARANNAHR AND THE ROLE OF ABDULLAH SUBAZMUNIY (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the flourishing of science and culture in Mawarannahr during the 9th–10th centuries, focusing in particular on the development of hadith scholarship in Bukhara. It analyzes the life of the renowned scholar Abdullah Subazmuniy and his pivotal role in the evolution of the Bukhara school of hadith. The article discusses how Subazmuniy attained the prestigious title “Ustoz” (the Teacher) and his activities at the Samanid court. It also critically examines the unfounded accusations leveled against him owing to the biased approach of certain traditionists, while underscoring the significance of his works in the Islamic world and his contribution to the development of the Hanafi school.
Keywords: Golden Age; mutabaʿa; shawahid; hadith schools